Frequency of Dyslipidemia in Patients Presenting with Nonalcoholic Fatty Liver Disease - Muhammad Imran Ullah, Gul-E Lala, Rashid Karim, Nayyar Zaman, Ibadulllah Jan, Annum Shahzadi (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Nonalcoholic fatty liver disease (NAFLD) is one of the most common causes of chronic liver disease in the developed world with increasing incidence among adults and children, and it is estimated to turn out leading cause for liver transplantation in America by end of this year1 It can present with variety of liver disease from nonalcoholic fatty liver (NAFL) to nonalcoholic steatohepatitis (NASH) and cirrhosis. Purpose of our study is to determine frequency of dyslipidemia in patients with nonalcoholic fatty liver disease2, although many studies had already been conducted on the same topic but no such study has been performed in our setup for the last many years. This study will give us the latest magnitude of dyslipidemia in patients with nonalcoholic fatty liver disease in our setup which will result in timely diagnosis, better management and future recommendations. Objective: To evaluate the frequency of dyslipidemia in patients presenting with nonalcoholic fatty liver disease at Hayatabad Medical Complex, Peshawar. Material and Methods: This cross sectional descriptive study was carried out at Gastroenterology Department, Hayatabad Medical Complex, Peshawar from Ist January 2022 to 31 June 2022. In the current study a total of 124 patients were observed. All the routine investigation, clinical examination and history were taken from the included patients as per hospital protocol. All the patients were subjected to radiology department for ultrasound of abdomen aimed at confirmation of nonalcoholic fatty liver disease. All radiological examination was done by an expert radiologist (FCPS) having at least 2 years of experience. 5 cc of blood sample was taken from the included patients and was referred to hospital laboratory for the diagnosis of dyslipidemia. Laboratory investigations were entirely done by expert pathologist (FCPS) having at least two years of experience. Dyslipidemia was considered positive if the lipid levels is other than the normal range in one or more laboratory tests. Results: In this study 22(18%) patients were in age range 18-30 years and 102(82%) patients were in age range 31-60 years. 38(31%) patients were male while 86(69%) patients were female. 33(27%) patients had duration of disease ≤ 5 year and 91(73%) patients had duration of disease > 5 year. 38(31%) patients had BMI ≤ 25 Kg/m2 while 86(69%) patients had BMI >25 Kg/m2. 82(66%) patients were diabetic while 42(34%) patients were not diabetic. 89(72%) patients were hypertensive while 35(28%) patients were not hypertensive. 32(26%) patients had dyslipidemia while 92(74%) patients didn’t had dyslipidemia. Conclusion: Our study concludes that frequency of dyslipidemia was 26% in patients presenting with nonalcoholic fatty liver disease at Hayatabad Medical Complex, Peshawar. Keywords: dyslipidemia, nonalcoholic, fatty liver disease.